TANGGUNG JAWAB PENGELOLA ARISAN ONLINE TERHADAP KERUGIAN PESERTA ARISAN AKIBAT TIDAK DIBAYARKANNYA IURAN ARISAN ONLINE DI KABUPATEN SANGGAU - NIM. A1012161165, EKO KRISTIAN TASLIM (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac There is a popular activity carried out by the community in Sanggau District at this time, namely online-based Arisan, a forum for carrying out social activities. Arisan is an activity in collecting money or goods that have value in the eyes of the community and the amount obtained will be given to someone who gets the arisan money. Young people in Sanggau District have a very high interest in Online Arisan because it makes other activities easier. This convenience occurs because only by using social media, Online Arisan participants can make transactions without having to meet face-to-face. With the online system, the activity of arisan is easier to do with a wider reach.The formulation of the problem in this research is